Methodology for a Large Scale Building Internet of Things Retrofit - Dzulkifly S.; Aris H.; Jorgensen B.N.; Santos A.Q. (Institute of Electrical and Electronics Engineers Inc., 2023)
Buildings; Energy efficiency; Energy utilization; Retrofitting; Sustainable development; Energy consumption datum; Internet of Things (IOT); Issues and challenges; Large scale buildings; Operational planning; Physical structures; Sensing technology; Systematic deployment; Internet of things